GLOBAL THREATS AND NATIONAL VALUES: A PHILOSOPHICAL INTERPRETATION OF SUSTAINABLE DEVELOPMENT - Ergashev Ulugbek Adxamovich (Modern American Journals, 2025)
This the article describes global processes philosophical content and their stable development concept with integral dependency seeing the current ecological, technological and social crises facing civilization are analyzed based on philosophical and ethical approaches. The scientific views of U. Beck, J. Habermas, H. Jonas, V. Stepin and N. Moiseyev, as well as the philosophical principles expressed in the Strategy of Uzbekistan “Uzbekistan – 2030”, the Concept of “Green Economy” and Decrees No. PF-60, PF-83, PF-158 are analyzed. The idea of sustainable development is interpreted based on harmony between man, society and nature, spirituality and social justice.
Keywords: Stable development, sustainable progress philosophy, global processes, ecological culture, spirituality values, social justice, technological development, West philosophy, CIS scientists, Uzbekistan experience, national Values, Responsibility principle, noosphere and biosphere, intercultural consensus